IDENTIFYING LEAD COMPOUNDS FOR POTENTIAL ANTI-TUBERCULOSIS DRUGS BY IN SILICO MYCOBACTERIUM TUBERCULOSIS SHIKIMATE KINASE INHIBITORS SELECTION OF CHEMICAL LIBRARY - NUGROHO, NUKI BAMBANG; ETIKA, BELLA; RAHAYU, SRI TEGUH; WIBOWO, AJI; SISKA, EKA (International Journal of Applied Pharmaceutics, 2025)
Objective: The present study aimed to identify Shikimate Kinase (SK) inhibitors as antitubercular agents from a chemical library by the utilization of molecular docking simulation, pharmacophore evaluation, and Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) prediction approaches. Methods: A molecular docking study by Molecular Operating Environment (MOE) was used to screen 400,000 compounds from the Mcule ULTIMATE Express 1 chemical library. This docking study used a rigid docking technique to simulate the interaction between receptors and compounds. The screened compounds were then validated by pharmacophore and ADMET analyses to show the presence of positive characteristics. Results: The result of molecular docking simulation identified N-[2-(diethylamino)ethyl]-2-(pyrrolidin-1-yl)acetamide as the most promising candidate for targeting Mycobacterium tuberculosis Shikimate Kinase (MtSK), due to its binding energy score (-11.3412 kcal/mol) and suitability of interacting residues (Asp34 and Gly80). Moreover, this compound also shared similar pharmacophores with shikimate, and it had positive drug-like and ADMET properties. Conclusion: This work identified one candidate for SK inhibitor from a pool of five drug-like hit compounds. These inhibitors show promise as prospective candidates for the development of a new anti-tuberculosis therapy and warrant additional experimental investigation.